Phosphorus fertilization in inbred and hybrid rice - Islam, MR; Saha, PK; Zaman, SK; Uddin, MJ (Dhaka University Journal of Biological Sciences, 2011)
Five phosphorus rates (0, 5, 10, 20 and 30 kg P/ha) were tested with four rice genotypes in Boro (BRRI dhan36, BRRI dhan45, EH1 and EH2) and T. Aman (BRRI dhan30, BRRI dhan49, EH1 and EH2) season. Phosphorus rates did not influence grain yield irrespective of varieties in T. Aman season while in Boro season P response was observed among the P rates. Application of P @ 10 kg/ha significantly increased the grain yield. But when P was applied @ 20 and 30 kg P/ha, the grain yield difference was not significant. The optimum and economic rate of P for T. Aman was 20 kg P/ha but in Boro rice the optimum and economic doses of P were 22 and 30 kg/ha, respectively. Hybrid entries (EH1 and EH2) used P more efficiently than inbred varieties. A negative P balance was observed up to 10 kg P/ha. Key words: Response; Phosphorus fertilizer; Inbred; Hybrid rice DOI: http://dx.doi.org/10.3329/dujbs.v19i2.8962 DUJBS 2010; 19(2): 181-187